Studi Kualitatif Keterlibatan Kader Posyandu Dalam Program Pencegahan Stunting - Irma Afifa; Ahisa Novianti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Posyandu cadres have a crucial role in preventing stunting, and this study was conducted to investigate their involvement at the Turen Community Health Center. The findings revealed that the posyandu cadres at the center were actively collaborating with the Family Assistance Team (TPK) formed by the BKKBN, as well as various other stakeholders, to collect data and screen for stunting prevention from preconception until toddlers reach 2 years old. However, a major obstacle in this program is the lack of reward system arrangements for the cadres. Despite their significant contribution to the success of the stunting prevention program, some cadres receive unequal workload and rewards. These findings can be utilized to further optimize cadre performance, and could serve as a valuable input for future research regarding the cadre reward system.